Wewenang dan Tanggungjawab Lembaga Manajemen Kolektif Nasional (LMKN) Dalam Perlindungan Hak Ekonomi Musisi Indonesia - Vira Nur Maharani; Dwi Desi Yayi Tarina (Fakultas Hukum, Universitas Warmadewa, 2024)
Currently, there are many musicians who use songs without permission from their creators. This phenomenon of copyright infringement is increasing in the music industry, where industry players use music and songs owned by creators for commercial purposes without permission and without paying the rightful royalties. As a result, many disputes arise between musicians. One example of a case involving music royalties and licensing is the dispute between Ahmad Dhani and former Dewa 19 vocalist, Once Mekel. This conflict arises because Once Mekel is suspected of singing Dewa 19 songs without permission from Dhani and without permission from the Indonesian Collective Management Organization for Music (LMK WAMI). The case was resolved through non-litigation mechanisms by reaching a peaceful agreement between both parties. The agreement allows Once to sing only one Dewa 19 song titled